Distal Axial Pin Lock without or with Nail Lock of Femoral Hybrid Intramedullary Nailing (FHIN) for Femoral Shaft and Distal Femoral Fractures - A Novel Technique of Distal Lock (Journal of Pakistan Orthopaedic Association, 2023)
Objective: A new technique of distal axial pin lock without or with nail lock for distal locking of femoral hybrid intramedullary nailing (FHIN) was devised for fixation of femoral shaft and distal femoral fractures. It could redress the difficulties of distal locking, hazards of extensive radiation exposure in lateral projection and the susceptibilities of screw/nail bend/break and mediolateral toggling of distal end of nail after conventional locking of femoral locked intramedullary nails (FLINS).Methods: 63 femoral shaft and distal femur fractures, treated by FHIN were prospectively assessed in this study. All FHIN implantations were distally locked with axial pin without or with nail lock depending on level and comminution of fracture. Axially stable femoral shaft fractures (FSFs) were distal locked with axial pin only. Axially unstable FSFs were distal locked with axial pin and oval nail hole. While distal femoral fractures were locked with axial pin and both oval and round nail holes. Postoperative assessment was made for accuracy of distal axial pin locking procedure. Technical distal axial pin lock problems and inability to find the nail slot were also recorded. Patients were followed until the time of solid union of fractures. During follow up X-rays patients were evaluated for complications of distal screw/nail bend /break and toggling of nail.Results: Of a total 63 distal axial pin lock procedures the accuracy of installation was 100% with single attempts and significantly shortened distal axial pin locking time. During follow up complications of distal axial pin/screw/nail bend/break, toggling of distal end of nail, distal migration of the nail, and loss of reduction were not noted. The number of radiation exposures, distal locking time and total operation time was significantly reduced as image intensifier use and its lateral adjustment was not required. The technique was quite easier and straightforward with shorter time period and learning curve.Conclusion: Primary distal axial pin lock without or with nail hole(s)lock of FHIN for treatment of femoral fractures can reduce the incidence of distal screw/nail bend/break and toggling of distal end of nail to the negligible extent. It also looks to be a predictable solution to decrease radiation dosage and its vulnerability during FHIN fixation by avoidance of image intensifier exposure and its lateral adjustment. Thus, reducing the radiation exposure and total surgical time.